Nutritional benefits and consumer acceptance of maize chips combined with alternative flours - Rodriguez-Miranda, Jesús; Peña Castellon, C. Meliza; Rivera Leiva, Miriam I.; Donovan, Jason A. (MDPI, 2025)
This study evaluated the nutritional composition, techno-functional properties, and sensory acceptance of tortilla chips made from alternative flours derived from local ingredients, including maize, beet, flaxseed, bean, and chia. Three blends were assessed: maize with beans, maize with beet, and maize with chia–flaxseed. Significant differences (p < 0.05) were observed in the flours’ moisture, ash, protein, lipid, and mineral content. Flaxseed flour exhibited the highest protein content (40.03 g/100 g), while chia flour was notable for its lipid (32.25 g/100 g) and fiber (38.51 g/100 g) content. Bean and chia flour were rich in iron and zinc. Sensory evaluations, conducted with 300 consumers in Honduras, revealed general acceptance of all blends, with maize chips enriched with chia–flaxseed showing the highest preference (47.2%). Approximately 50% of participants reported consuming tortilla chips weekly, prioritizing taste, freshness, and price. Notably, over 40% expressed willingness to pay a premium for more nutritious, baked options. These results underscore the potential of alternative flours to enhance local diets and foster healthier eating habits. Moreover, the positive consumer response highlights a significant market opportunity for small and medium-sized enterprises (SMEs), promoting awareness of nutrition and public health in Honduras.